Health care information systems : a practical approach for health care management - Wager, Karen A., 1961-; Lee, Frances Wickham, 1953-; Glaser, John P. (John Patrick), 1955- (San Francisco : Jossey-Bass, 2013)
"The revised third edition of Health Care Information Systems is a comprehensive text that offers an understanding of health care information systems that helps readers work effectively with and support information systems design, as well as the development and implementation. It covers current and developing information systems of interest to managers in health services organizations; health care information systems architecture; security and privacy issues; uses of health care information for clinical and strategic analysis and decision support; techniques for developing and evaluating an information system request for proposal; and information on the future"--Provided by publisher.
Includes bibliographical references and index.
Nursing
Keywords: Health Information Systems -- organization & administration